Existence of arrow-debreu equilibrium with generalized stochastic differential utility - Patrick Beißner (Bielefeld University, Institute of Mathematical Economics (IMW), 2011)
This paper establishes, in the setting of Brownian information, a general equilibrium existence result under a stochastic differential formulation of intertemporal recursive utility. The present class of utility functionals is generated by a backward stochastic differential equation and incorporates preference for the local risk of the stochastic utility process. The setting contains models in which Knightian uncertainty is repre- sented in the subjective and objective sense.
Keywords: 330; BSDE; GSDU; super-gradients; properness; general equilibrium; Knightian uncertainty; Allgemeines Gleichgewicht; Nutzen; Analysis; Stochastischer Prozess; Risiko; Theorie